Digitalization of Islamic Finance: Epistemological Study of the National Sharia Board-Indonesian Council of Ulama’s Fatwa - Hidayati, Tri; Hidayatullah, Muhammad Syarif; Komarudin, Parman; Atika, Atika (Al-Ahkam, 2023)
The dynamic and rapid development of digital business and finance requires progressive Sharia legal certainty. National Sharia Board-Indonesian Council of Ulama (Dewan Syariah Nasional – Majelis Ulama Indonesia/DSN-MUI) has issued several fatwas related to digital finance. This research aims to examine the portrait of DSN-MUI’s progressiveness towards the digital finance paradigm and aspects of Islamic legal epistemology in the DSN-MUI Fatwa with the theme of digital finance. This research uses a qualitative approach. The primary data for this research are the DSN-MUI fatwas up to 2021 with a digital theme, plus secondary data in the form of relevant literature. Data analysis uses content analysis techniques. The findings are that there are three DSN-MUI fatwas regarding digital finance in Sharia financial institutions, namely Fatwa No. 116/DSN-MUI/IX/2017, No. 117/DSN-MUI/II/2018, and No. 140/DSN-MUI/VIII/2021. These three fatwas constitute progressive Islamic business law and are important for the Sharia financial industry in Indonesia. DSN-MUI used the ta’līlī and istiṣlāḥi methods with the consideration that electronic money, digital-based financing, and crowdfunding are permissible (mubah) based on sharia principles to achieve benefit. These three DSN-MUI fatwas need to be transformed into OJK regulations and can become a source for making derivative fatwas.